Arts-Based LearningImage as a Vehicle for Transformation in Adult Learners - Dianna Bartel (Adult Education Research Conference, 2015)
This study will consider the use of arts-based learning as a means of provoking transformation in the lives of adult students in non-arts classrooms and community environments. Specifically considering the use of image as the vehicle encouraging transformation.
Keywords: arts-based learning; image; visual-ethnography; transformational learning